Measurement error in stylised and diary data on time use - Man Yee Kan; Stephen Pudney (University of Essex, Institute for Social and Economic Research (ISER), 2007)
We investigate the nature of measurement error in time use data. Analysis of stylised recall questionnaire estimates and diary-based estimates of housework time from the same respondents gives evidence of systematic biases in the stylised estimates and large random errors in both types of data. We examine the effect of these measurement problems on three common types of statistical analyses in which the time use variable is used as: (i) a dependent variable, (ii) an explanatory variable, and (iii) a basis for cross-tabulations. We develop methods to correct the biases induced by these measurement errors.
Keywords: 330